2008
DOI: 10.1152/ajpregu.00833.2007
|View full text |Cite
|
Sign up to set email alerts
|

Chronic diet-induced hyperhomocysteinemia impairs eNOS regulation in mouse mesenteric arteries

Abstract: Looft-Wilson RC, Ashley BS, Billig JE, Wolfert MR, Ambrecht LA, Bearden SE. Chronic diet-induced hyperhomocysteinemia impairs eNOS regulation in mouse mesenteric arteries. Am J Physiol Regul Integr Comp Physiol 295: R59 -R66, 2008. First published April 30, 2008 doi:10.1152/ajpregu.00833.2007.-Hyperhomocysteinemia (HHcy) impairs endothelium-dependent vasodilation by increasing reactive oxygen species, thereby reducing nitric oxide (NO ⅐ ) bioavailability. It is unclear whether reduced expression or function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
23
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 34 publications
8
23
0
Order By: Relevance
“…In four of the groups the baseline diameter after 30 min of equilibration at 37° C was either not changed ( PE5 : 229 ± 8 μm; PE15 : 235 ± 7 μm), or increased slightly but significantly (p<0,05, paired t-test) ( NT : 235 ± 5 μm; PE+ACh : 245 ± 8 μm), indicating an absence of basal tone, which is consistent with our previous results (Looft-Wilson et al, 2008). However, the L-NAME and Denuded groups had significantly decreased (p<0.05, paired t-test) diameters after the 30 min equilibration ( L-NAME : 195 ± 11 μm; Denuded: 198 ± 12 μm), indicating basal nitric oxide release from the endothelium in this artery type.…”
Section: Methodssupporting
confidence: 92%
“…In four of the groups the baseline diameter after 30 min of equilibration at 37° C was either not changed ( PE5 : 229 ± 8 μm; PE15 : 235 ± 7 μm), or increased slightly but significantly (p<0,05, paired t-test) ( NT : 235 ± 5 μm; PE+ACh : 245 ± 8 μm), indicating an absence of basal tone, which is consistent with our previous results (Looft-Wilson et al, 2008). However, the L-NAME and Denuded groups had significantly decreased (p<0.05, paired t-test) diameters after the 30 min equilibration ( L-NAME : 195 ± 11 μm; Denuded: 198 ± 12 μm), indicating basal nitric oxide release from the endothelium in this artery type.…”
Section: Methodssupporting
confidence: 92%
“…Elevated cGMP levels in response to ACh stimulation are an indirect measure of the activation of eNOS. In resistance microvessels, we have previously reported significantly lower basal expression of eNOS and the pS1179eNOS-to-eNOS (activation site) ratio in mice with diet-induced HHcy with no difference in the pT495eNOS-to-eNOS (deactivation site) ratio (101). S1179 eNOS phosphorylation was also significantly less in these vessels when they were stimulated with ACh, both ex vivo and in situ.…”
Section: Endothelial Dysfunction In Cbs Deficiencymentioning
confidence: 77%
“…The antieNOS antibodies recognized a specific immunolabeled band around 130 kDa (Fig. 3A) corresponding to the reported molecular mass of murine eNOS (19,34). Densitometric analysis revealed that eNOS expression levels were reduced by ϳ40% in the aortic endothelium of Cx40 Ϫ/Ϫ mice compared with Cx40 ϩ/ϩ mice (Fig.…”
Section: Expression Of Enos Is Decreased In the Aortic Endothelium Ofmentioning
confidence: 87%